Breakthrougs in authors` lives –from archeology of a notion to research practice - Całek, Anita (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
The article is a proposal to renew the scope of the semantic concept of breakthrough, taking into account the familiar and absent semantic fields of an old Polish verb `przełomić`. The archeology of this notion allows us to see the ambiguity and ambivalence of the breakthrough phenomenon as well as to show it in a singular context, field and domain – all of which are necessary in biographical research. Their practical use in the multidimensional sense of the breakthrough is devoted to the last part of the discussion.